Pleistocene faunas of "Glyfada" cave, Diros, Laconia - ΣΥΜΕΩΝΙΔΗΣ, Ν. Κ.; ΓΙΑΝΝΟΠΟΥΛΟΣ, Β. Ι. (Bulletin of the Geological Society of Greece, 2018)
The cave of "Glyfada" is located in Mani peninsula, in the perfecture of Laconia, about 2 km. north to the Municipality of Diros. It was discovered in 1923 by the local agents of the town, but it has been systematically studied since 1949 up to now; a corridor-with the secondary developments-of 10.606 m. length has been surveyed and mapped, while it was found that there is a part of 1833 m. being submarine. The cave has been developed in semi-crystallized Upper Cretacean and Eocean limestones of Mani Unit; it develops a labyrinth like morphology. The first paleontological findings are reported in 1957-58,by Petrochilos, the first geologist who discovered the cave. Since 1994, there has been ongoing a systematic study of the environment of the cave, while, in thirteen different sites in the cave, a large amount of bones was located, attributed to prehistoric mammals and specifically to Hippopotammus amphibius LINNE, although the new evidence provides data for a new species. It was also located the species Martes foina ERXLEBEN, Dama dama LINNE, a fragment of the upper jaw RUMINANDIA, bones of birds, the carnivore Panthera sp., Panthera leo LINNE, Crocuta crocuta ERXLEBEN and, lastly, Monachus monachus. The taxonomic identification was conducted in the Paleontological Laboratory of the University of Athens and the Institute of Paleontology in Vienna. The dating was undertaken in the Centre of Isotopie Research in the University of Groningen in Holland.